Cohort Profile: The Incarcerated Serious and Violent Young Offender Study - McCuish, Evan (Journal of developmental and life-course criminology, 2022)
In this profile, we describe how the Incarcerated Serious and Violent Young Offender Study (ISVYOS) leveraged detailed administrative data to create a prospective longitudinal study. We also discuss the research and policy context at the time the ISVYOS was initiated, its methodology, and what has been learned so far. The ISVYOS includes 1,719 participants who were incarcerated in adolescence and followed through adulthood. Between 1998–2002 (Cohort I) and 2005–2011 (Cohort II), male and female youth were recruited for interviews that measured various risk and protective factors, experiences in custody, and attitudes towards the justice system. Follow-up data include measures of justice system involvement, risk assessment data, and social network data. Participants were an average age of 30.57 (SD = 4.65) as of December 2019. Over 90% of the sample was involved in the adult justice system. So far, research using ISVYOS data has addressed the reliability and validity of measures of psychopathy in adolescence, justice system criminal careers, risk factors for chronic and persistent offending, and the adult offending outcomes of youth involved in serious offenses (e.g., sexual offenses and homicide offense). Inquiries regarding data access should be sent to the first author.